The DK children's illustrated dictionary - McIlwain, John. (Boston : Distributed by Houghton Mifflin, 1994)
Children's dictionary with captioned photographs and illustrations. Includes word groupings by theme and guides to spelling and word building.
Booklist.
Library Talk.
Wilson's Children.
3.5.
3.5
K-3
Keywords: English language -- Dictionaries, Juvenile; English language -- Dictionaries; Picture dictionaries; English language -- Dictionaries; Picture dictionaries